Circular Dichroism Studies at Variable Temperature: Urobilinoid Conformation - Lightner, David A. (1970)
Measurements of the temperature dependence of the circular dichroism spectra of l-stercobilin and d-urobilin show that the conformations of these optically-active urobilinoids change with temperature between 163 and 297°K. These conformational changes depend critically on the hydrogen bonding characteristics of the solvent. Thus, in methanol-glycerol (9:1), the chiral sense of the helical conformation of the dipyrrylmethene chromophore is reversed on lowering the temperature, whereas in chloroform, reversal does not occur.